Systematic review of therapy for neurogenic detrusor overactivity - Fowler, Clare J. (Canadian Urological Association Journal, 2013)
While many neurologic diseases predispose patients to neurogenic detrusor overactivity (NDO), the only populations that have been systematically studied are adults with multiple sclerosis (MS), adults with spinal cord injury (SCI) and children and young adults with myelodysplasia. First-line pharmacotherapy for NDO is an antimuscarinic drug. However, the evidence base for these agents in this indication is poor. There is some high-quality evidence for the efficacy of detrusor injections of botulinum toxin A in the treatment of NDO, with significant reduction in urgency incontinence episodes, improved urodynamic parameters, and improved quality of life. While few adverse events have been reported with this therapy, there is a need for intermittent self-catheterization in these groups.